VMware performance and capacity management : master SDDC operations with proven best practices - Rahabok, Iwan (Professional expertise distilled., 2016)
Master SDDC Operations with proven best practices About This Book Understand the drawbacks of the traditional paradigm and management that make operations difficult in SDDC Master performance and capacity management in Software-Defined Data Center Operationalize performance and capacity monitoring with proven dashboards Who This Book Is For This book is primarily for any system administrator or cloud infrastructure specialist who is interested in performance management and capacity management using VMware technologies. This book will also help IT professionals whose area of responsibility is not VMware, but who work with the VMware team. You can be Windows, Linux, Storage, or Network team; or application architects. Note that prior exposure to the VMware platform of data-center and cloud-based solutions is expected. What You Will Learn Simplify the task of performance and capacity management Master the counters in vCenter and vRealize Operations and understand their dependency on one another Educate your peers and management on SDDC Operations Complete your SDDC monitoring to include non-VMware components Perform SDDC performance troubleshooting Explore real-life examples of how super metric and advanced dashboards Introduce and implement a Performance SLA Accomplish your Capacity Management by taking into service tiering and performance SLA In Detail Performance management and capacity management are the two top-most issues faced by enterprise IT when doing virtualization. Until the first edition of the book, there was no in-depth coverage on the topic to tackle the issues systematically. The second edition expands the first edition, with added information and reorganizing the book into three logical parts. The first part provides the technical foundation of SDDC Management. It explains the difference between a software-defined data center and a classic physical data center, and how it impacts both architecture and operations. From this strategic view, it zooms into the most common challenges - performance management and capacity management. It introduces a new concept called Performance SLA and also a new way of doing capacity management. The next part provides the actual solution that you can implement in your environment. It puts the theories together and provides real-life examples created together with customers. It provides the reasons behind each dashboard, so that you get the understanding on why it is required and what problem it sol...